2018
DOI: 10.1007/s10113-018-1378-7
|View full text |Cite
|
Sign up to set email alerts
|

Participatory ecosystem service mapping to enhance community-based mangrove rehabilitation and management in Demak, Indonesia

Abstract: Assessment of mangrove ecosystem services (ES) is essential to understand and manage the contribution of these ecosystems to the well-being of local communities. They are the primary beneficiaries but their experience, knowledge, and information are frequently ignored in ES assessment and mapping. In this study, a participatory resource mapping (PRM) approach was applied using local knowledge and experience to analyze geo-referenced information on mangrove ecosystem services. Local communities were involved fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…This experience had contributed to increased insights of the value of mangroves in protecting their villages and lives from flooding. A similar result was reported by Damastuti and de Groot [49], who showed that the incidence of coastal hazards, such as storms and tsunamis, make coastal communities value mangrove ecosystem services, such as coastal protection. Furthermore, during the FGDs, all local communities perceived that mangrove forests contributed to the formation of rainfall and thus provided suitable climatic conditions for agricultural activities.…”
Section: Awareness Of Mangrove Ecosystem Services and Their Relative Importancesupporting
confidence: 86%
“…This experience had contributed to increased insights of the value of mangroves in protecting their villages and lives from flooding. A similar result was reported by Damastuti and de Groot [49], who showed that the incidence of coastal hazards, such as storms and tsunamis, make coastal communities value mangrove ecosystem services, such as coastal protection. Furthermore, during the FGDs, all local communities perceived that mangrove forests contributed to the formation of rainfall and thus provided suitable climatic conditions for agricultural activities.…”
Section: Awareness Of Mangrove Ecosystem Services and Their Relative Importancesupporting
confidence: 86%
“…202 Crucial to the co-production of data is what happens to it afterwards: communities must have equal access to the data they help produce, rather than enabling the "extraction" of such data from communities. 203…”
Section: Joint Inspections Monitoring and Fact-findingmentioning
confidence: 99%
“…NTFPs from mangroves include many animal products, but animal products are generally fisheries-related (mangrove finfish, shrimp, crabs, bivalves and gastropods) and their economic significance is much better documented than plant-related NTFPs. Often, there are production data particularly for the most important finfish, shrimp, crabs and mollusks [36,[84][85][86], even if they generally still tend to be poorly documented. In this paper, we focus on non-destructive plant-related products and uses.…”
Section: Role Of Mangrove Ntfps and Plurality Of Potentialmentioning
confidence: 99%
“…Such lack of alignment or "scale mismatch" between ecologically-connected systems and management boundaries creates major social and ecological complexities for management [31,32]. This challenge of proper distribution of accrued benefits resulting from nature-based mangrove management has spurned various community-based and benefit-sharing approaches (e.g., community-based forest management, bio-rights) as means to ensure that mangrove management benefits and costs are more equitably spread amongst all stakeholders [13,[33][34][35][36]. Likewise, the Forest Department of Bangladesh (FD) [37] highlighted the need to share the benefits of forest wild harvest among the communities living around the Sundarbans mangrove forest.…”
Section: Introductionmentioning
confidence: 99%